Day of the Week and Month of the Year Effects in the Indian Commodity Market - Jampala, Rajesh C.; Adi Lakshmi, P.; Kishore, O. A. R. (Indian Journal of Research in Capital Markets, 2014)
This paper empirically investigated the day of the week effect and month of the year effect on the returns of the Indian commodity market indices with special references to the Multi Commodiy Exchange. Ordinary least squares dummy variable regression model with GARCH(1,1) coefficients was used to identify day of the week and month of the year anomalies. The conditional auto regressive models were used to overcome the impact of heteroscedasticity on the time series data to capture the true calendar effects in the commodity markets in India. The results indicate that day of the week and month of year effects are present in the commodity market after adjusting the returns to the heteroscedasticity. The agricultural, metal, and energy indices showed different day and month effects. No significant weekend and year end effects were observed in the commodity market index returns.